Nutrient activation of Trichoderma fungal spores for improved biocontrol activity - Linda Gordon Hjeljord; Arne Tronsmo (浙江大学学报. 农业与生命科学版, 2004)
The effect of preliminary nutrient activation on the ability of conidia of the antagonist Trichoderma harzianum P1 (ThP1) to suppress Botrytis cinerea was investigated in laboratory, greenhouse and field trials. Preliminary nutrient activation at 21 ℃ accelerated subsequent germination of the antagonist at temperatures from 9 ℃ to 21 ℃; at≥ 18 ℃ the germination time of preactivated ThP1 conidia did not differ significantly from that of B. cinerea. When coinoculated with B. cinerea, concentrated inocula of preactivated but ungerminated ThP1 conidia reduced in vitro germination of the pathogen by ≥ 87% at 12 ℃ to 25 ℃; initially-quiescent conidia achieved this level of suppression only at 25 ℃. Application of quiescent ThP1 conidia to detached strawberry flowers in moist chambers reduced infection by B. cinerea by ≥85% at 24, but only by 35% at 12 ℃. Preactivated conidia reduced infection by ≥60% at 12 ℃. Both quiescent and preactivated conidia significantly reduced latent infection in greenhouse-grown strawberries at a mean temperture of 19 ℃, while only preactivated conidia were effective in the field at 1a mean temperature of 14 ℃ on the day of treatment application.Trichoderma biocontrol isolates are most effective as highly concentrated inocula. Their antagonism to other fungi may be a result of pregermination respiration. In a nutrient-rich medium, almost all Trichoderma atroviride P1 (P1) conidia initiated germination processes and increased respiration, even in dense suspensions. When 1 × 107 P1 conidia per mL were coinoculated with 1 × 105B. cinerea conidia per mL, dissolved oxygen fell to <1% within 2 h and the pathogen failed to germinate. More dilute P1 suspensions consumed oxygen slowly enough to allow coinoculated B. cinerea to germinate. On nutrient-poor media, fewer P1 conidia initiated germination. Oxygen consumption by the inoculum and inhibition of B. cinerea were enhanced when P1 conidia were nutrient-activated before inoculation. Pregermination respiration also affected the competitive capacity of the antagonist on solid substrates, where respiratory CO2 stimulated germination rate and initial colony growth. These parameters were directly correlated with inoculum concentration (R2≥ 0.97, P<0.01). After initiating germination, Trichoderma conidia became more sensitive to desiccation and were killed by drying after only two hours incubation on a nutrient-rich substrate at 23 ℃. Consideration of these effects of germination initiation on the competitive potential of Trichoderma in biological control will bee discussed.